Effects of Embodiment-Based Learning on Perceived Cooperation Process and Social Flow. (25th July 2015) - Wei, Chun-Wang; Chen, Hsin-Hung; Chen, Nian-Shing
Abstract: Peer interaction plays an important role during the learning process. Currently predominant paradigm of digital learning materials limits learners' interaction with their peers using traditional user interfaces. To cope with this problem, this study proposes an embodiment-based learning environment to facilitate more peer interactions. The effectiveness of the environment is evaluated by designing an electronic circuit learning activity and through a control-experimental group experiment, including 80 voluntary participants randomly assigned to the "embodiment-based learning group" and "traditional learning group." Three variables, learning performance, perceived cooperative perception and social flow were assessed. Results show that there is no significant difference among the two groups in learning performance; however, participants in the embodiment-based learning group have higher perceived cooperation process and social flow during learning process than the traditional learning group.